2015
DOI: 10.1186/s12889-015-1712-7
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of snacks to dietary intake and their association with eating location among Norwegian adults – results from a cross-sectional dietary survey

Abstract: BackgroundSnack consumption has been reported to increase over recent decades. Little is known about possible associations between snack composition and snack eating location. In the present study, we aimed to describe the contribution of snacks to dietary intake in Norwegian adults and to investigate whether the composition of snacks differed according to where they were eaten.MethodsDietary data were collected in 2010 and 2011 using two telephone administered 24 h recalls about four weeks apart. In total, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 28 publications
7
33
0
5
Order By: Relevance
“…31 Some recent studies have shown that snack consumption can contribute more than 20 % to the daily energy intake. 32,33 Considering these findings on their fatty acid profiles, popular packaged salty snack products in Serbia could significantly contribute to the overall daily intake of SFAs and t-FAs.…”
mentioning
confidence: 99%
“…31 Some recent studies have shown that snack consumption can contribute more than 20 % to the daily energy intake. 32,33 Considering these findings on their fatty acid profiles, popular packaged salty snack products in Serbia could significantly contribute to the overall daily intake of SFAs and t-FAs.…”
mentioning
confidence: 99%
“…Nevertheless, only a limited number of studies have been conducted to date to examine meal and snack eating behaviours in relation to overall diet and health markers (4)(5)(6)(7) , mainly because there is no consensus about what constitutes a snack, a meal or an eating occasion (3) . Although some researchers have relied on respondents' self-identification of meals, snacks or eating occasions (4)(5)(6)(8)(9)(10)(11)(12)(13)(14) , others have attempted to use more objective criteria (based on clock time, energy content/contribution or both) (5)(6)(7)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) . An accurate distinction between meals and snacks is important, because they are hypothesised to have different effects on energy and nutrient intakes (7,27,28) .…”
mentioning
confidence: 99%
“…
Winter Meeting, 4-5 December 2018, Optimal diet and lifestyle strategies for the management of cardio-metabolic risk Office cake culture: an exploration of its characteristics and associated behaviours and attitudes among UK office workers and implications for workplace healthThe workplace is an important setting for the promotion of healthy lifestyle choices (1) . Eating frequency and energy intake from snacking have risen in recent decades (2) with cakes and similar sweet baked goods the primary energy contributors to snack food (3) . Providing such foods for colleagues to share, 'office cake' (OC), is a prominent form of workplace snacking and is speculated to lead to increased energy intake and obesity (4) .
…”
mentioning
confidence: 99%